2014
DOI: 10.1093/nar/gku758
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the seven valine tRNAs in Escherichia coli involves novel features of RNase P

Abstract: Here we report that RNase P is required for the initial separation of all seven valine tRNAs from three distinct polycistronic transcripts (valV valW, valU valX valY lysY and lysT valT lysW valZ lysY lysZ lysQ). Particularly significant is the mechanism by which RNase P processes the valU and lysT polycistronic transcripts. Specifically, the enzyme initiates processing by first removing the Rho-independent transcription terminators from the primary valU and lysT transcripts. Subsequently, it proceeds in the 3′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…In vitro structure−function studies demonstrate that sequence variation at 5′ leader nucleotides involved in both RNA−RNA and RNA−protein interactions can have significant functional effects on RNase P processing rates as well as cleavage site specificity. 9,21,29 For example, analysis of 5′ leader point mutations and amino acid substitutions in P protein support favorable hydrogen bonding interactions between an adenosine at N(−4) and the protein subunit of Bacillus subtilis RNase P; however, the sequence preference of E. coli RNase P at this position is diminished. 9 Additionally, mutation of the 5′ leader at N(−1) showed altered processing rates and that are partly rescued by compensatory mutations P RNA in J5/ 15.…”
mentioning
confidence: 99%
“…In vitro structure−function studies demonstrate that sequence variation at 5′ leader nucleotides involved in both RNA−RNA and RNA−protein interactions can have significant functional effects on RNase P processing rates as well as cleavage site specificity. 9,21,29 For example, analysis of 5′ leader point mutations and amino acid substitutions in P protein support favorable hydrogen bonding interactions between an adenosine at N(−4) and the protein subunit of Bacillus subtilis RNase P; however, the sequence preference of E. coli RNase P at this position is diminished. 9 Additionally, mutation of the 5′ leader at N(−1) showed altered processing rates and that are partly rescued by compensatory mutations P RNA in J5/ 15.…”
mentioning
confidence: 99%
“…Processing mechanisms for tRNAs and sRNAs have been defined, particularly for transcripts terminated by RITs in E. coli (57, 66-70). Recent work has demonstrated that Rho terminated transcripts have processed 3’ ends immediately downstream of a stable stem-loop (71).…”
Section: Discussionmentioning
confidence: 99%
“…3C). Some require the initial removal of the Rho-independent transcription terminator by RNase E before RNase P can process the rest of the transcript (64, 65, 67). The RNase P cleavages occur at the mature 5′ termini (65), while RNase E cleavages, with the exception of the three proline tRNAs (63), leave extra nucleotides downstream of the CCA determinant (11, 66).…”
Section: Enzymes Involved In Transfer Rna Processingmentioning
confidence: 99%
“…The RNase P cleavages occur at the mature 5′ termini (65), while RNase E cleavages, with the exception of the three proline tRNAs (63), leave extra nucleotides downstream of the CCA determinant (11, 66). A surprising observation from the RNase P processed transcripts was that the enzyme cleaves the polycistronic transcripts starting from the 3′ terminus and not the 5′ terminus (64). …”
Section: Enzymes Involved In Transfer Rna Processingmentioning
confidence: 99%
See 1 more Smart Citation